Tinjauan Tentang Penyerahan Uang Panjar Dalam Transaksi Jual Beli Hak Atas Tanah Di Kawasan Pariwisata : Studi Kasus di Desa Sekongkang Bawah, Kecamatan Sekongkang, Kabupaten Sumbawa Barat, Provinsi Nusa Tenggara Barat - Meilani Putri, Nanda; Wahyuddin, Wahyuddin (Fakultas Hukum Universitas Mataram, 2024)
The objective of this study is to investigate the motivations and legal consequences arising from the advance payment in land sale transactions in Sekongkang Bawah Village, Sekongkang District. This study employs empirical legal research with legislative, conceptual, and sociological approaches. The findings indicate that the reasons for making an advance payment in land sale transactions are rooted in longstanding cultural practices and are influenced by business factors, financial considerations, the buyer’s character, pricing factors, and the economic conditions of both the seller and the buyer. The legal consequences of making an advance payment are that both parties, the seller and the buyer, are bound by the down payment agreement and cannot sell the land to another party. However, in practice, two issues had been identified: first, the seller had no right to sell inherited land because the name on the certificate was the heir's name; second, the seller unilaterally revoked the sale without the buyer's consent, causing financial loss. Then, the buyer nullified the sale agreement by filing a lawsuit in court, seeking compensation and penalties for the canceled transaction.